A big data services platform framework towards cloud manufacturing system. (2017) - Li, Yongfeng; Zhang, Yongping
The source of big data in cloud manufacturing (CMfg) is analysed from two aspects. First, manufacturing cloud service lifecycle and manufacturing entire lifecycle, as well as its characteristics. Then, the classifications of big data resource and big data resource services in the CMfg are investigated respectively and the relationship between them as well. After analysing the requirements for big data technology in CMfg system, a framework for big data resource service platform is established, as well as its service operation model. The key technologies for implementing the proposed framework are studied and the application process of the platform is illustrated from the perspective of supply-demand matching of cloud services.